2019
DOI: 10.1007/s10804-019-09336-x
|View full text |Cite
|
Sign up to set email alerts
|

Aging Parents’ and Middle-Aged Children’s Evaluations of Parents’ Disability and Life Problems

Abstract: Aging parents' and middle-aged children's evaluations of parents' disability and life problems

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…Consistent with the recent study by Lee et al ( 2020 ), reporting that adult children tended to perceive their older parents’ functional limitations more seriously than their parents did, the current study’s participants reported that their parents were not aware of their functional decline or the potential negative consequences of their behaviors. This perception gap between older parents and adult children is markedly similar to governance transfer in adolescence and early adulthood.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Consistent with the recent study by Lee et al ( 2020 ), reporting that adult children tended to perceive their older parents’ functional limitations more seriously than their parents did, the current study’s participants reported that their parents were not aware of their functional decline or the potential negative consequences of their behaviors. This perception gap between older parents and adult children is markedly similar to governance transfer in adolescence and early adulthood.…”
Section: Discussionsupporting
confidence: 85%
“…Unfortunately, scaffolding is frequently mismatched, resulting in tension between older parents and adult children (Fingerman et al, 2011 ; Lee et al, 2020 ). One source of this tension is the difference in perspectives and priorities of older adults and their children.…”
Section: Tension and Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…While adult children living separately from parents may be able to provide more economic support than coresident adult children (Gao et al, 2012), their needs for instrumental and emotional support may not be met (Gao et al, 2012). Although adult children may provide emotional support by telephone or social media, such as WeChat in contemporary China, older persons are much less likely to use virtual networks (Knodel & Pothisiri, 2015), and the reduced frequency of interactions may impair family ties and reduce wellbeing (Lee et al, 2020). The fact that nonresident adult children offer more upward support and receive less downward support may reduce their wellbeing, and we assume applies to both sons and daughters.…”
Section: Hypothesesmentioning
confidence: 99%